Biallelic β‐carotene oxygenase 2 knockout results in yellow fat in sheep via CRISPR/Cas9. (16th November 2016) - Niu, Y.; Jin, M.; Li, Y.; Li, P.; Zhou, J.; Wang, X.; Petersen, B.; Huang, X.; Kou, Q.; Chen, Y.
Summary: The recently emerged CRISPR/Cas9 approach represents an efficient and versatile genome editing tool for producing genetically modified animals. Β‐carotene oxygenase 2 (BCO2) is a key enzyme in the progress of β ‐carotene metabolism and is associated with yellow adipose tissue color in sheep. We have recently demonstrated targeted multiplex mutagenesis in sheep and have generated a group of BCO2 ‐disrupted sheep by zygote injection of the CRISPR/Cas9 components. Here, we show that biallelic modification of BCO2 resulted in yellow fat, compared with the fat color in monoallelic individuals and wild types (snow‐flower white). We subsequently characterized the effects of gene modifications at genetic levels employing sequencing and Western blotting, highlighting the importance of the BCO2 gene for the determination of fat color in sheep. These results indicate that genetic modification via CRISPR/Cas9 holds great potential for validating gene functions as well as for generating desirable phenotypes for economically important traits in livestock.